Pengaruh CRM Sebagai Strategi Keunggulan Bersaing Syaria Untuk Meningkatkan Loyalitas dan Penjualan (Studi pada Distributor Suku Cadang Kendaraan Roda Dua di Jawa Tengah) - Theresya Amelia Prabowo; I Made Bayu Dirgantara (Jurnal Ilmiah Ekonomi Islam, 2023)
This study aims to conduct research related to the influence of CRM as a competitive advantage strategy to increase loyalty and sales (a study on two-wheeled vehicle parts distributors in Central Java). The research method used in this research project is qualitative and quantitative research. The research conducted will use SMART PLS. The results show that based on the t test table, the effect of the CRM variable on Competitive Advantage is 0.000 t-table (1.96), where Ho is rejected and Hypothesis 1 is accepted. Based on the t-test table, the effect of the CRM variable on Customer Loyalty is 0.014 t-table (1.96), where Ho is rejected and Hypothesis 2 is accepted, which means that there is an effect of CRM on customer loyalty. the calculated t value is 4,407 > t table (1.96), where Ho is rejected and Hypothesis 3 is accepted, which means that there is a competitive advantage effect on customer loyalty. of 2,491 > t table (1.96), where Ho is rejected and Hypothesis 4 is accepted, which means that there is an effect of Competitive Advantage on Increase in Sales.Based on the t test table, the effect of the variable Customer Loyalty on Increase in Sales is 0.274 > 0.050 while the t value is 1.094 < t table (1.96), where Ho is accepted and Hypothesis 5 is rejected, which means that there is no effect of Customer Loyalty on Increase in Sales.